Analyzing CO2 concentration changes and their influencing factors in Indonesia by OCO-2 and other multi-sensor remote-sensing data - Shuai Yin; Xiufeng Wang; Heri Santoso; Hiroshi Tani; Guosheng Zhong; Zhongyi Sun (International Journal of Digital Earth, 2018)
We used OCO-2 products and considered three factors that potentially affect CO2 concentration in Indonesia: sea surface temperature (SST), forest fires and vegetation. From 2014 to 2016, CO2 concentration in Indonesia showed a trend of increase, which is consistent with the global increase reported by the Greenhouse Gases Observing Satellite (GOSAT) Project. As an archipelago country, the results indicate that SST has a direct effect on the CO2 concentration in Indonesia. Their changing exhibits similar fluctuations; meanwhile, CO2 concentration and SST also presented positive correlation. In 2015, the number of fire hotspots suddenly increased to 140,699, because of occurrence of the worst forest fire. Due to special geographic conditions, forest fires did not induce CO2 concentration changes in Indonesia, but CO2 concentration in the corresponding islands showed a trend of increase. CO2 concentration increased in Kalimantan during the occurrence of forest fire in September–October 2014, and CO2 concentration increased in Kalimantan and Sumatra during the occurrence of forest fire in September–October 2015. Vegetation indices were stable and presented no correlation with CO2 concentration. This study demonstrated that OCO-2 is capable of monitoring CO2 concentration at a regional scale; additionally, an effective method for using OCO-2 Level 2 products is proposed.